Chronodisruption and Loss of Melatonin Rhythm, Associated with Alterations in Daily Motor Activity and Mitochondrial Dynamics in Parkinsonian Zebrafish, Are Corrected by Melatonin Treatment - Paula Aranda-Martínez; José Fernández-Martínez; Yolanda Ramírez-Casas; César Rodríguez-Santana; Iryna Rusanova; Germaine Escames; Darío Acuña-Castroviejo (MDPI AG, 2023)
Beyond sleep/wake, clock genes regulate the daily rhythms of melatonin production, motor activity, innate immunity, and mitochondrial dynamics, among others. All these rhythms are affected in Parkinson's disease (PD), suggesting that chronodisruption may be an early stage of the disease. The aim of this study was to evaluate the connection between clock genes and these rhythms in PD, and whether melatonin administration reestablished the normal clock function. Parkinsonism was induced with 600 μM MPTP (N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) in 24-120 h post fertilization (hpf) zebrafish embryos and melatonin was administered at a dose of 1 μM. Day-night melatonin rhythm disappeared in MPTP-treated embryos, which showed an advance in the activity phase in parallel with changes in the rhythm of clock genes. An alteration in the fission-to-fusion mitochondrial dynamics was also detected in parkinsonian embryos, increasing the former and leading to apoptosis. Melatonin administration to MPTP-treated embryos fully restored the circadian system, including the rhythms of clock genes, motor activity, melatonin rhythm, and mitochondrial dynamics, and decreasing apoptosis. Because clock-controlled rhythms such as sleep/wake alterations are early events in PD, the data here reported may point to chronodisruption as one initial pathophysiological event of the disease.